Délimitations et défenses du territoire : les conditions d’émergence de la linguistique nord-américaine au début du XXe siècle - Henri Le Prieult (Anglophonia)
American linguistics seem to have had, from the very start, a strong relationship with America as a territory. From the first works of anthropologists who had to deal with the "Amerindian imperative," to the development of a "ho-me-grown structuralism" (Harris 1993), there seems to have been an enduring link between the emergence of a specifically American linguistic school of thought and the very conditions the land of American offered to the many amateurs and scientists who considered and analysed the facts of language from the XVIth century onwards. Through three distinct yet deeply interrelated chronological stages, this paper attempts to give an overview of the different historical, geographical and institutional frameworks which conditioned the progressive foundation of American linguistics.